Doing a research project in sport performance analysis - O'Donoghue, Peter; Holmes, Lucy (Teacher in performance analysis); Robinson, Gemma (Abingdon, Oxon ; New York, NY : Routledge, 2017)
"The research project or dissertation is a core component of any degree programme in the rapidly developing discipline of sport performance analysis. This highly practical and accessible book provides a complete step-by-step guide to doing a research project. Showcasing the very latest research methods, it covers the whole research process, from identifying a research question and system development to data collection, data analysis and writing up the results. Introducing the fundamentals of project planning and management, this book highlights the importance of research ethics and explains the differences between successful undergraduate and postgraduate projects. Full of expert advice and original insights that can be applied to theoretical and empirical research projects, it covers all the key aspects of conducting a degree-level research project, including: selecting a research topic and writing a research proposalworking with a supervisorunderstanding research ethicsimplementing best practices for project managementcollecting, interpreting and presenting results. Doing a Research Project in Sport Performance Analysis is an indispensable guide for any student, lecturer or practitioner working in sport performance analysis."--Provided by publisher.
Sports performance analysis research -- Sports performance analysis research topics -- Enterprise and development projects -- The research proposal -- Ethics -- System development -- Data gathering and analysis -- Writing up the dissertation.
Keywords: Sports sciences -- Research; Sports -- Physiological aspects